Perbandingan Hasil Belajar Siswa Menggunakan Modul Elektronik dengan Modul Konvensional Melalui Model Guided Discovery Learning pada Materi Senyawa Hidrokarbon - Risa Tri Fadilah; Latisma Dj (Universitas Batanghari Jambi, 2023)
This research is a quasi-experimental research. This study was conducted to reveal how the students' learning outcomes on hydrocarbon compounds were compared when using an electronic module with a conventional module with a guided discovery learning model in class XI of SMAN 3 Pariaman. This study used a two-group pretest-posttest design with 66 students in class XI MIPA 1 and XI MIPA 2 at SMAN 3 Pariaman for the academic year 2022/2023. Class XI MIPA 1 is used as experimental class 1 using electronic module teaching materials, while class XI MIPA 2 is used as experimental class 2 using conventional module teaching materials. The data obtained from student learning outcomes in the experimental class 1 is 80.3030 and in the experimental class 2 is 71.8181. From hypothesis testing with a significance level of 0.05, it was obtained tcount < ttable (1.59 < 2.04). So in this study H1 was accepted. Thus, there is a significant difference in learning outcomes between classes using electronic modules with guided discovery learning models and classes using conventional modules with guided discovery learning models on hydrocarbon compounds in class XI IPA SMAN 3 Pariaman in the 2022/2023 academic year.